Are there predictor variables for the diagnosis of transthyretin cardiac amyloidosis?. (14th October 2021) - Goena, C; Arana, X; Villanueva, I; Solla, I; Rengel, A; Querejeta, R
Abstract: Introduction: Transthyretin cardiac amyloidosis (ATTR) can be reliably diagnosed in the absence of histology if grade 2 or 3 cardiac uptake is demonstrated on 99mTc-DPD scan (DPD) in the absence of a detectable monoclonal component. Diagnosis requires a high degree of clinical suspicion in the presence of often non-specific findings and that it may be one of the reasons to under-diagnose ATTR. The aim of the study is to identify clinical, analytical and ECG variables that best predict a positive DPD result. Methods: This is a multicentre retrospective study including all patients undergoing consecutive 99mTc-DPD scintigraphy in a reference area of 750, 000 inhabitants between January 2016 and January 2021 for suspected ATTR. AL amyloidosis patients were excluded. Clinical, analytical, ECG and echocardiographic data were analyzed. We identified variables that independently predicted a positive DPD study using a multivariable logistic regression analysis. Receiver Operating Curve (ROC) analysis and the Area under the Curve (AUC) were calculated to assess the discrimination capacity of the model to predict a positive DPD study. Results: DPD scans from a total of 181 patients were analyzed. Mean age of the sample: 78 years (42–96), 100% caucasians, 77% male. 54.7% (N=99) had a positive DPD study (defined as grade 2 or 3 Perugini uptake) and 45.3% (N=82) were negative. Independent predictors of a positive study were age, male gender, left ventricular septum thickness, any grade of atrioventricular block, low QRS voltage, Carpal tunnel syndrome, history of hypotension or need to lower antihypertensive drugs and a NT-proBNP value above 1800 pg/ml (See Table 1). The diagnostic accuracy of the model was excellent, with an AUC of 0.92 (IC 95% 0.87–0.96) (see Figure 1). Conclusions: There are clinical-analytical factors and ECG and echocardiogram findings accessible in daily clinical practice that are able to predict a positive result on cardiac scintigraphy requested for suspected ATTR. Identifying these factors may improve the non-invasive diagnosis of ATTR. Funding Acknowledgement: Type of funding sources: None.